KUALITAS GURU AGAMA KRISTEN DI SEKOLAH MENENGAH PERTAMA SEKOTA BANJARBARU BERDASARKAN KONSEP KEGURUAN YESUS DALAM INJIL YOHANES - Lianto, Lianto; Windarti, Maria Titik (Sekolah Tinggi Teologi Kadesi Bogor, 2023)
A high-quality education will produce a well-educated pupil as well. Of course this is not apart from the human resources that play a role in the educational unit as an educator. As a teacher of Christianity education must have adequate ability in teaching, both scientifically disciplined and spiritually the teacher. At the present time there are still many problems arising in the world of education in Indonesia. It is also not apart from the Primary Secondary School of Banjarbaru City specifically Christian education that exists in the City of banjarbaru. The results of a survey of 10 teachers of Christian education at Banjarbaru Primary High School as respondents showed that there are still Christian teachers in the city that do not have the professionalism in teaching based on the concept of Jesus' supremacy in John 13:12-20 and have not had the basic competence under Act No. 14 of 2005 scientifically. This research uses qualitative research with techniques in data collection through interviews, observations and documentation studies. The aim of this research is to find out how much the quality of PAK teachers in the first secondary school in Banjarbaru city, and what the impact of when a teacher has quality on PAK learning in the city of Banjerbaru. It turns out there was a positive influence on Christian education in Banjarbaru City's First High School when a teacher had good qualities and focused.